Contempt of Court as Defined in “Contempt of Courts Act 1971 - Samantasinghar, Jajati Keshari (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2017)
Contempt of Courts means any act that interferes and obstructs in the process of administration of Justice or undermines or lowers the authority & dignity of the courts and bring them into disrespect and disrepute. It is therefore, necessary that courts are vested with the power to punish for committing the offence of contempt of court. In India the first statute to deal with the offence of contempt of court was contempt of court Act 1926. After independence the Contempt of Court Act 1952 was enacted. However one common lacunae was conspicuous in both the earlier Act. Both the Contempt Act 1926 & 1952 did not define the offence of Contempt. On the basis of Sanyal Committee report & Joint selected Committee known as Bharghab Committee the Contempt of Court Act 1971 was brought in incorporating the definition of Contempt in clear and definite terms.